(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The present investigation highlights the formulation and evaluation of matrix tablets of propranolol hydrochloride (HCl) using a natural polymer, is gum kondagogu. Materials and Methods: Wet granulation method was used for the preparation of matrix tablets of propranolol HCl using varying proportions of natural polymer as a release retardant, Avicel pH 102 as diluent, talc and magnesium stearate as glidant and lubricant respectively. Total 12 formulations (PG1-PG12) were prepared by using different proportions of drug and gum kondagogu (1:0.5, 1:1, 1:1.5, 1:2) with the aid of granulating fluids such as distilled water, ethanol and isopropyl alcohol. Granules of propranolol HCl formulations were evaluated for pre-compression parameters and flow properties. All the prepared matrix tablet formulations after compression subjected for physico-chemical evaluation of hardness, friability, thickness, weight variation, drug content, swelling index and in vitro drug release studies. Results and Discussion: The distinguishable difference in the results was shown to be dependent on characteristics and composition of polymer concentrations. Based on in vitro drug release the polymer gum kondagogu showed better dissolution control in all formulations, which is result of its release retardant characteristics. The formulations PG4, PG8 and PG12 (drug:polymer ratio 1:2) have shown more than 95% drug release for 12 h and hence PG10 (drug:polymer ratio 1:1) was selected for further studies. The selected formulation PG10 studied for the effect of electrolytes (sodium carbonate, calcium carbonate, magnesium carbonate) on release of drug by employing in different concentrations (25, 50 and 75 mg). These electrolytes were employed to examine matrix swelling and gel properties. Swelling study suggested that when the matrix tablets come in contact with the medium, they take up medium and swells, forming a gel layer around the matrix and simultaneously erosion also takes place. Fourier transform infrared spectra revealed that there was no interaction between drug and polymers. Drug release analysis was confirmed that there exists a significant difference in the measured Higuchi rate constant among the matrices. Conclusion: The combination of both hydrophilic natural polymer and electrolytes successfully employed for formulating the sustained release matrix tablets of propranolol HCl.